Situação epidemiológica da filariose linfática no foco endêmico de Maceió-Alagoas após a implantação do programa de eliminação - Lima, Ana Rachel Vasconcelos de (2007)
Lymphatic filariasis is a neglected disease popularly known as elephantiasis because of one of its chronic clinical manifestation. In Maceió, filariasis transmission is restricted to a well defined area in the city including the contiguous and central ditricts of Feitosa, Jacintinho and Pitanguinha, at the edge of Canal do Reginaldo. In order to assess the epidemiological situation of lymphatic filariasis in Maceió after the implementation of the "Program to Eliminate Lymphatic Filariasis" (PELF) in the city in 1999, hemoscopic and immunological surveys were conducted. For the hemoscopic survey (HS) blood sample was collected by the thick smear (TS) technique after after 9h30 pm, and examined for the presence of circulating microfilariae (mf). Using this technique 53,857 individuals in the endemic area and 9.880 inhabitants in the neighbouring area were examined, aged four years or older. Immunological survey (IS) was carried out using a rapid immunochromatographic card test ("ICT card test") to examine 414 inhabitants of the endemic area and 2,541 in the neighbouring area, being 2,214 individuals between 15 and 25 years and 327 children between 5 and 10 years old. By TS, 182 (0,32%) out of the 53,857 examined individuals in the endemic area presented microfilariae, being the prevalence significantly higher among male than female. It was observed along the years the following frequencies of microfilaraemic carriers: 1999 – 0.76%; 2000 – 0.57%; 2001 – 0.49%; 2002 – 0.11%; 2003 – 0.13%; 2004 – 0.06%. Among 9,880 individuals examined in the neighbouring area, only one (0,01%) microfilaremic carrier was detected. Only one (0,24%) filarial antigen carrier out of 414 examined, were detected. In neighbouring area, 327 children were examined for the "ICT card test", all being antigen-negative, while 2,214 young adults examined, eight (0,36%) presented soluble antigens. The average of microfilariae density of 93.8 ± 149.1 mf/mL blood, is significantly lower than that observed in the same area, in the past decade of 580.5 ± 786 mf/mL. During the study carried out since the implementation of the PELF in Maceió, from 1999 until 2006, the prevalence rates of microfilaraemic diagnosed by TS in the endemic area presented a significant decrease. Analysing the results of examined individuals from the neighbourhood of the endemic area it is evident that filariasis do not spread to the contiguous districts of the endemic focus. The IS carried out in individuals above five years of age in the general population of the endemic area detected very low antigenaemia for Wuchereria bancrofti in 2003. The IS in the neighbouring area carried out in children of 5-10 years old did not detect any individual with circulating antigen of W. bancrofti, whereas in the group of young adults (15-25 years), in this same area, eight individuals were found antigenpositive, being six amicrofilaraemic and two with low microfilaraemia when examined by TS usually employed in big surveys. The results of this study prove that measures used for the elimination of Bancroftian filariasis in the endemic focus of the disease in Maceió, as the treatment and accompaniment of the microfilaraemics since the implementation of the PEFL in 1999, were effective to control transmission in the studied area, making possible its elimination.